Malaysia’s “Corporate Directors Training Programme” as an example of senior executive training: suggestions for specific and general improvements with insights from knowledge management - Ei, Sun Oh; Chai, Madeline; Ei, Fun Oh (2004)
Malaysia’s Corporate Directors Training Programme (CDTP) aims to increase the awareness of company directors towards good corporate governance.In this paper, observations will be shared and suggestions for improvement (partly based on insights from knowledge management) made on both the overall structure of CDTP and specifically its corporate governance component, so that the participating directors may more readily immerse in the subjects.The paper’s discussion also shed lights on the lack of proper corporate information and knowledge management in Malaysia.It is proposed that the corporate-governance module be redesigned into three smaller units emphasizing both principles and practices.Moreover, the CDTP course materials should be shortened and include exercises and evaluation.It is envisioned that the revamped CDTP will more effectively achieve the goal of fostering a more healthy business environment in Malaysia.